Application of Five Finger Hypnosis and Mozart Music Therapy Towards Reducing Pain Scale in Post-Surgery Ca-Mammae Patients - Adinda Bella Maharani; Bagas Biyanzah Drajad Pamukhti; Isti Wulandari (Jurnal Kegawatdaruratan Medis Indonesia, 2026)
Background: Breast cancer is a malignant tumor in the breast that invades the area around the breast and spreads throughout the body. Breast cancer is the second largest cause of death worldwide, with 2.3 million deaths in 2022. Pain is one of the many impacts experienced after breast cancer surgery. One way to reduce this pain is by non-pharmacological means. Therefore, it is necessary to apply the non-pharmacological technique of 5-finger hypnosis and Mozart music therapy. Purpose: To determine the results of the application of 5-finger hypnosis and Mozart music therapy on reducing the pain scale in post-operative breast cancer patients in the Flamboyan of Dr. Moewardi Surakarta Hospital. Method: This research method is a descriptive case study to address problems in patient nursing care. The number of respondents was 2. Results: The study found that pain levels increased from before to after the application. The development was measured using the NRS score. Conclusion: Pain levels decreased in patients in the Flamboyan 5 before and after 5-finger hypnosis with Mozart music.